2022
DOI: 10.1158/0008-5472.can-22-1888
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Rare Haplotypes Associated with Breast Cancer Risk

Abstract: Numerous common genetic variants have been linked to breast cancer (BCa) risk, but they only partially explain the total BCa heritability. Inference from Nordic population-based twin data indicates rare high-risk loci as the chief determinant of BCa risk. Here, we use haplotypes, rather than single variants, to identify rare high-risk loci for BCa. With computationally-phased genotypes from 181,034 white British women in the UK Biobank, a genome-wide haplotype-BCa association analysis was conducted using slidi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Therefore, haplotypes can assist in identifying rare variants that have a potential impact on phenotypic traits. ( Bloom et al., 2019 ; Wainschtein et al., 2022 ; Wang et al., 2023 ). Furthermore, especially in highly quantitative traits like yield where markers tend to have very small effects on traits, haplotype blocks can identify positive or negative chromosomal segments.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, haplotypes can assist in identifying rare variants that have a potential impact on phenotypic traits. ( Bloom et al., 2019 ; Wainschtein et al., 2022 ; Wang et al., 2023 ). Furthermore, especially in highly quantitative traits like yield where markers tend to have very small effects on traits, haplotype blocks can identify positive or negative chromosomal segments.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the confidence in our chr11 discoveries, we next sought to apply Chromosome Overlap in a region known to contain a rare risk haplotype. Our recent genome-wide rare-haplotype analysis discovered by a sliding-window approach six loci containing rare haplotypes which were associated with increased breast cancer risk in both UKBB and DRIVE ( Wang et al, 2023 ). The lead 50-SNP haplotype (by P -value) discovered at chromosome 22q12, called h38, had a frequency of 10.6 per 10,000 chromosomes and an HR of 2.81 ( P = 1.2 × 10 −14 ).…”
Section: Resultsmentioning
confidence: 99%
“…FOXA1-binding occurred in a region devoid of any UKBB-typed SNPs, but without any coincident peaks belonging to other factors. A more intense Hi-C block occurred downstream of h1 and h38 in a region spanned by the original 250-SNP haplotype ( Wang et al, 2023 ). The comparative lack of features about h1 and h38 suggested that the binding events at the chr11 locus may have been specific to regulation of CCND1 and that some other biological mechanism would have to be sought at the chr22 locus, as explored in our previous study ( Wang et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations